Management of the historic center of San Luis of Potosí - Arias Suárez, Thalía (2019)
Mexico is one of the countries with the greatest number of historic centers recognized by UNESCO, and thus has developed a series of cultural policies, which deal with the regulatory aspect as well as with the economic resources of these centers. The following article analyzes the management of the historical centers of San Luis de Potosí, located in the north of the country. Heritage recovery was carried out within the framework of national cultural policies and local regulations. In what follows, the documents referring to the management work have been reviewed, which have taken into consideration the political, social, cultural and economic aspects of the Historical Center. Likewise, the realization of the proposed plans has been analyzed, as well as the effects of these on the heritage and local actors. In addition, a review of the management of the historical center of San Luis de Potosí has been carried out, which highlights the successes and failures of the hard work involved in the management of cultural heritage within a space where so many cultural and social elements are concentrated.